The persistence of the housewife ideology: Shifts in women's roles in production of Sumbanese handwoven cloth. (December 2022) - Gajjala, Radhika; Faniyi, Ololade Margaret; Ford, Sarah; Untari, Rustina; Al Makmun, Muhammad Taufiq
This article examines women's shifting roles in the production of handwoven cloth in Sumba, Indonesia. The main themes that emerge are the invisible labor of women and the production of a self-empowered entrepreneurial, gendered, laboring subjectivity that works in tandem with a housewife ideology firmly situated in a 'new' liberal patriarchy. The inequalities emerging from these shifts are parallel to inequalities produced through neoliberalization of global south craft communities in a context of global markets and tourist-oriented production. The discussion in this article is based on case studies drawn from over 50 interviews conducted during field visits and continued remotely when away from the field in Lambanapu and Praillu regions in Waingapu of Sumba, Indonesia. Overall, our analysis reveals how cultural work in this global south context reproduces a Westernized, neoliberal patriarchy even as it allows for individualized expressions of women's agency.`